POPULATION DYNAMICS OF THE MONSOON RIVER PRAWN, MACROBRACHIUM MALCOLMSONII IN CAUVERY RIVER, TAMIL NADU - VENKATASAMY, M.; JAWAHAR, P.; JAYAKUMAR, N.; DEVARAJ, M. (Journal of the Inland Fisheries Society of India, 2021)
Population dynamics of Macrobrachium malcolmsonii was studied from the Cauvery river Tamil Nadu. Juveniles were dominant during September - December and adults during June - August. Annual k and mean t0 estimated were 45.95 cm 0.2184 year-1 and (-) 0.5201 respectively. The Z, M and F were 1.265, 0.9 and 0.365 respectively. First recruitment was at 1.67 months and its first capture was at the age of 2.68 months. Potential yield per recruit was 32 g. MSY was 2.75 t at 0.6 E level. At the present E level of 0.3, the fishery was in an underexploited state.Key words: Macrobrachium malcolmsonii, population dynamics, MSY, Cauvery river.